Analisis Wacana Kritis Novel Egosentris Karya Syahid Muhammad dalam Perspektif Literasi Kritis Pembelajaran Bahasa Indonesia - Farah Zhifa; Lina Sundana (Jumper: Journal of Educational Multidisciplinary Research, 2026)
This study is motivated by the importance of developing critical literacy in Indonesian language learning through literary texts that represent social realities. The novel Egosentris by Syahid Muhammad presents various discourses related to power relations, empathy crisis, and ideological construction in contemporary society. This research aims to analyze the discourse in the novel Egosentris using Norman Fairclough’s three-dimensional model of Critical Discourse Analysis and to examine its relevance from the perspective of critical literacy in Indonesian language education. The research employs a descriptive qualitative method with documentation as the data collection technique, while data analysis is conducted through textual analysis, discourse practice, and sociocultural practice. The findings indicate that the novel represents ideologies of individualism, normalization of power relations, and social criticism through reflective and critical language use. Furthermore, the novel has strong potential as teaching material to foster students’ critical thinking skills. This study concludes that Critical Discourse Analysis of literary texts can effectively support critical literacy-based Indonesian language learning